1993
DOI: 10.1002/apmc.1993.052060101
|View full text |Cite
|
Sign up to set email alerts
|

Removal of escherichia coli from water by systems based on insoluble poly(glycidyl methacrylate)‐G‐tetraethylenepentamine and ‐G‐polyethylenimine

Abstract: A study was made of the removal of Escherichia coli (E. coli) from water by systems based on insoluble poly(glycidy1 methacrylate)-g-tetraethylenepentamine and -gpolyethylenimine, i. e., the reaction products of insoluble poly(glycidy1 methacrylate) (PGMA) beads with tetraethylenepentamine (TEP) or polyethylenimine having molecular weights of about 600 (PEI600). The polymers (PGMA-TEP and PGMA-PEI600) were brought into contact with E. coli in sterilized physiological saline. These polymers made the viable cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Then, PEI600 or TEP was incor-porated to the MR polymer beads (150-300 lm). [95] Their probable structures are shown as 68 ( Figure 43). Since the beads were so hard and scarcely swell in solvents, the amounts of reacted PEI600 and TEP were small, particularly gel type beads reacted scarcely with TEP or PEI600.…”
Section: Macromolecules Based On Poly(glycidyl Methacrylate)mentioning
confidence: 99%
“…Then, PEI600 or TEP was incor-porated to the MR polymer beads (150-300 lm). [95] Their probable structures are shown as 68 ( Figure 43). Since the beads were so hard and scarcely swell in solvents, the amounts of reacted PEI600 and TEP were small, particularly gel type beads reacted scarcely with TEP or PEI600.…”
Section: Macromolecules Based On Poly(glycidyl Methacrylate)mentioning
confidence: 99%
“…So far, insoluble carriers such as cellulose, starch, agarose, porous glass, and cross-linked styrene/divinylbenzene have been used as carriers for the immobilization of antibiotics, l6,I7 metallorganic compounds, 7*8 and quaternary ammonium salts?, [18][19][20][21] In addition, the antimicrobial activity of cross-linked 4-vinyl alkylpyridinium salts has been reported, 22 but later investigations demonstrated that this effect was due to adsorption of cells to the surface.23 Recently, insoluble polymer beads based on crosslinked polystyrene-polyethyleneimine polymers, 24,25 on poly ( glycidyl methacrylate ) -tetraethylenepentamine, 26 and on activated alumina-supported poly ( styrene-co-chloromethylstyrene ) 27 were investigated for the removal of bacteria from water. A decrease of viable cell numbers was observed, due to the adsorption of cells to the surface of these polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, insolubilized agents having antibacterial activity have been developed 1–7. Insolubilized agents having positively charged groups, such as quaternary ammonium groups and phosphonium groups, or triethylenetetramine side chains, thiol groups, and phenol derivatives are reported to exhibit high antibacterial activity 8–12.…”
Section: Introductionmentioning
confidence: 99%